Structural equation modeling of health belief, intention, health promoting behaviour, social support, symptom severity and quality of life among people with abdominal bloating in Kelantan - Ab.Lah, Nurzulaikha Mahd (2021)
Abdominal bloating (AB) is regarded as one of the common bothersome symptoms by people of diverse backgrounds and all ages worldwide. However, there were still limited validated measures to explore the psychological behaviour of people with AB and its relationship with the outcome measures, such as psychological well-being, symptom severity and quality of life (QoL). This research aimed to develop validated measures for Bloating Health Belief, Intention, Bloating Health Promoting Behaviour, Bloating Social Support, Pictogram AB, Bloating Severity Questionnaire, Bloating Quality of Life and to examine the relationship between health belief, intention, health promoting behaviour, social support, symptom severity and QoL among people with AB in Kelantan. The study consisted of three phases, Phase I: Questionnaires development and translation; Phase II: Exploratory study by validating questionnaires through the exploratory factor analysis (EFA); and Phase III: Confirmatory study consisting of the validity of the measurement model with confirmatory factor analysis (CFA) and structural equation modeling (SEM) model development. The purposive sampling method was used in recruiting the participants for Phase II and Phase III. A cross-sectional study design was employed in all three phases. In Phase I, four new Malay language questionnaires were developed through literature search, experts‘ input and in-depth interviews. Besides, the English version of the Pictogram AB, Bloating Severity Questionnaire and Bloating Quality of Life were translated into Malay version. All of the questionnaires were examined for content validity based on experts‘ opinion and then pre-tested by the participants. In Phase II, all newly developed and translated questionnaires (except for intention as it consisted of one item and Pictogram AB) were tested for construct validity through exploratory factor analysis (EFA) and the reliability of internal consistency based on Cronbach alpha was reported. In Phase III, validity of the measurement models with CFA were confirmed for all the measures tested in Phase II, which were then used in a SEM analysis to determine the inter-relationships among the study variables. The validated Hospital Anxiety and Depression Scale was used to measure the anxiety and depression of the participants. Statistical analysis for Phase II and Phase III were performed by using SPSS 26 and Mplus 8, respectively. The newly developed and translated questionnaires were content validated based on seven experts‘ opinion and were comprehended by 30 participants during the pre-testing process. There were 152 participants with a mean age of 31.27 years old (standard deviation, (SD) = 14.36) and 323 participants with a mean age of 27.69 years old (SD = 11.50) participated in Phase II and Phase III studies. In Phase II of the exploratory study, the final models were established with all factor loading and Cronbach alpha showing evidence of validity and reliability for the questionnaires tested. Next, final measurement models of CFA with acceptable fit indices were obtained in Phase III of the confirmatory analysis. The final CFA measurement models were included in the SEM model, which explained the connections between the study variables. The final SEM model indicated good fit based on several fit indices and 15 significant path relationships were established. The final SEM model explained the variance of the social support by 16%, intention by 39%, and QoL by 53.8%. Significant relationships were found between severity general towards QoL, social support and intention towards severity general, health belief towards social support, depression and health belief towards severity 24 hours, health belief towards intention and health promoting behaviour, intention and health promoting behaviour towards depression and intention towards health promoting behaviour. The newly developed and translated questionnaires were considered to be valid and reliable in the assessment of health belief, intention, health promoting behaviour, social support, symptom severity and QoL among people with AB in Kelantan. The SEM model indicated that there were some inter-relationships between the study variables and there were significant contributing factors influencing the symptom severity and QoL of people with AB. The present study provides valuable insight to the health care providers in reducing the symptom severity and improving QoL among people with AB.